Global Change and Educational Reform in Ontario and Canada - O’Sullivan, Brian (Canadian Journal of Education/Revue canadienne de l'éducation, 1999)
Canadian education has been responding to global change for many decades. Over the last 30 years, two global paradigms have dominated debates about education in Ontario and in Canada. The first paradigm, global economic competitiveness, maintains that knowl- edge has become the competitive advantage of industrial nations in the global economy and that utilitarian principles should guide our educational reforms. The second paradigm, global interdependence, holds that we should acknowledge our interdependent global needs and responsibilities and that this should guide our educational reforms. I argue that to prepare students for the global challenges of the new century, excellence in education should be defined as meeting the requirements of both paradigms and as including the study of all major global change — economic and technological — as well as the study of world cultures, politics, ecology, and humanitarian issues. Depuis les 30 dernières années, deux paradigmes dominent les débats sur l’éducation en Ontario et dans l’ensemble du Canada. Le premier paradigme, la mondialisation de la compétitivité économique, maintient que la connaissance est devenue l’avantage concur- rentiel des pays industrialisés dans l’économie mondiale et que des principes utilitaires devraient guider les réformes en éducation. Le second paradigme, l’interdépendance à l’échelle mondiale, soutient que nous devrions reconnaître l’interdépendance de nos besoins et de nos responsabilités à l’échelle mondiale et que c’est ce principe qui devrait guider les réformes en éducation. L’auteur avance pour sa part que pour préparer les élèves aux défis mondiaux du nouveau siècle, l’excellence en éducation devrait être définie en fonction des exigences des deux paradigmes, ce qui suppose l’étude des changements économiques et technologiques à l’échelle mondiale ainsi que l’étude des diverses cultures, de la politique, de l’écologie et des questions humanitaires.